ANALYZING THE SOCIAL RETURN ON INVESTMENT OF THE UMA PALAK LESTARI ECOTOURISM CSR PROGRAM OF PT. PERTAMINA PATRA NIAGA DPPU NGURAH RAI - Susatyo, Adhi; Anna, Zuzy; Hasyir, Dede Abdul; Komarulzaman, Ahmad (Sosiohumaniora, 2025)
This study evaluates  PT. Pertamina Patra Niaga DPPU Ngurah Rai’s  ecotourism Corporate Social Responsibility (CSR) program using  Social Return on Investment (SROI). The study evaluates program outcomes over 2020–2023 and  projects potential impacts for 2024, involving 14 stakeholders through field observation, interviews, and document review. The program generated total benefit  of IDR 3,291,026,216 with an SROI ratio of 3.35, meaning that every IDR 1 invested yields IDR 3.35 in combined economic, social, and environmental benefits. Farmers were the main beneficiaries while sustainability compass analysis shows  the economic impacts dominate due to the greater measurability of financial outcomes compared to social and environmental effects. The findings underscore the value of SROI as an integrative evaluation approach in the Indonesian CSR context and indicates that strengthening community capacity, institutional support, and market access is crucial for ensuring the long-term sustainability of program impacts.